The implementation of Hikayat Raja Bersiong mythology through comic; understanding the perception among students about local mythological stories through comic / Muhammad Ricky Iskandar Samsudin - Samsudin, Muhammad Ricky Iskandar (2014)
Malay mythological and legendary stories has many of interesting stories. However, most of the young generation nowadays has a lack of knowledge and awareness about the Malays mythological and legendary stories. Thus, the aim of this research is to study and analyze the implementation of the Malays mythology literature of Hikayat Raja Bersiong in a form of action comics. In this context, the researcher intends to understand the perception among the student regarding the story of Hikayat Raja Bersiong which will be created in comic form. In additional the study also wants to analyze the student's general knowledge and perception about the local comic genres. Generally, this research is a case study among the certain group of people. In order to obtain the data: the researcher frequently used a qualitative research method to observe the scenarios that are related to his topic Thus, reliable information was gathered from the books, articles and internet in order to analyze the literature reviews of the study. Besides, the researcher also used a quantitative research method to gain the raw data about his respondents. The researcher used survey questionnaires as an instrument to collect the data.